Can migration reduce educational attainment ? evidence from Mexico - McKenzie, David; Rapoport, Hillel; World Bank. (Washington, D.C. : World Bank, 2006)
"The authors examine the impact of migration on educational attainment in rural Mexico. Using historical migration rates by state to instrument for current migration, they find evidence of a significant negative effect of migration on schooling attendance and attainment of 12 to 18 year-old boys and 16 to 18 year-old girls. IV-Censored Ordered Probit results show that living in a migrant household lowers the chances of boys completing junior high school and of boys and girls completing high school. The negative effect of migration on schooling is somewhat mitigated for younger girls with low educated mothers, which is consistent with remittances relaxing credit constraints on education investment for the very poor. However, for the majority of rural Mexican children, family migration depresses educational attainment. Comparison of the marginal effects of migration on school attendance and on participation in other activities shows that the observed decrease in schooling of 16 to 18 year-olds is accounted for by the current migration of boys and increased housework for girls. "--World Bank web site.
Title from PDF file as viewed on 8/28/2006.
Includes bibliographical references.
Also available in print.
System requirements: Adobe Acrobat Reader.
Mode of access: World Wide Web.
Zahid
Keywords: Educational attainment -- Mexico; Mexico -- Emigration and immigration; Mexico -- Rural conditions